Determinants Of Youth Sexual Behaviour And Its Implications To Reproductive And Sexual Health Policies And Services In Central Java - Antono Suryoputro; Nicholas J Ford; Zahroh Shaluhiyah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2006)
Background : Indonesian young people have been facing significant challenges to their health and well-being. This situation has causing an increased vulnerability to health hazards of various kinds, specially related to reproductive and sexual health, including the growing threat of HIV/AIDS. These adolescent health issues, most of which are preventable, can lead to significant morbidity and mortality.Method : This paper reports on findings from a recent study, which seeks to identify predictor factors of youth sexual behaviour and their need for services, in order to derive practical policy for enhancing youth sexual and reproductive health services. Involving a total 2000 sample derived from youth population aged 18-24 years old. 1000 samples were each randomly selected from factory employers and university students.Result : The findings show that the overall pattern of sexual and reproductive youth health risk is relatively low in comparison to that in many other countries, this is partly related to distinctive and positive characteristics of the culture of Central Java. The findings also showthat Self-efficacy is the strongest predictor of youth sexual behaviour.This study recommends that future policy and program should address how to protect oneself if engaging in sex, rather than only focusing on how to abstain from sex. Such policies and program development should be addressed to the ways to maintaining young people’s positivenorms and values in line with existing culture and religion by enhancing their self efficacy and life-skill through school-based sexual and reproductive health education and services.Keywords : Health services, reproductive and sexual health, sexual behaviour, javaneseyouth.